Pengembangan Desain Pembelajaran Blended Learning dan Media Interaktif Pengukuran Berat Benda di Sekolah Dasar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2025)
This research is motivated by the need for innovation in mathematics learning in elementary schools, especially regarding material measuring the weight of objects which is often considered abstract by students. The aim of this research is to develop a learning design based on blended learning combined with interactive media to increase understanding of concepts and student involvement in the learning process. The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, Evaluation) development model. The findings show that the learning design developed is classified as very feasible and effective based on the assessment of material experts, media, as well as the results of limited trials in the field. The use of interactive media in a blended learning approach has been proven to significantly increase students' learning motivation and understanding of concepts. The implications of this research indicate that the integration of digital technology in mathematics learning in elementary schools can be an eee3werfgfdzxczalternative solution to create a more interesting, interactive and meaningful learning experience.